Editor’s Note - Isa, Che Ruhana; Sulaiman, Ainin; Chan, Wai Meng (Asian Journal of Business and Accounting, 2015)
It is our pleasure to present the second issue of Volume 8 of the Asian Journal of Business and Accounting (AJBA). The Faculty of Business and Accountancy, University of Malaya, first published AJBA in 2008. In 2010, AJBA was submitted for consideration to be included in Scopus, and in 2011 the journal was accepted for coverage starting with the first issue published in 2008. The year 2015 sees a new milestone. The Web of Science has selected AJBA for indexation in its new database, the Emerging Sources Citation Index (ESCI). In addition, AJBA is also indexed in Asean Citation Index (ACI), as well as ERA. We would not be able to achieve this recognition without the unrelenting support of our past and present international advisory board members, chief and area editors as well as reviewers. To our advisers, editors and reviewers, we wish to thank you for your tireless effort. We also wish to thank researchers for their contribution of papers to AJBA, and for their trust in the journal’s rigorous reviewing process that aims to uphold the quality of the papers published in AJBA. We also wish to record our appreciation to the Malaysian Accountancy Research and Education Foundation (MAREF) for the financial support provided. In this issue of AJBA, six papers are presented. All the papers convey the findings of collaboration between researchers from different institutions. The publication of Koh, Mohan, and Tan is duly appropriate in view of the current debate on systemic risk which highlights the importance of risk management function and governance. After reviewing prior literature and interviewing ten chief risk officers, Koh et al. propose a comprehensive approach for competency development of risk management function of banks. In the corporate world, crucial lessons can also be learned from past scandals which reveal the importance for auditors to have a high level of ethical behaviour. In the second paper, Haron, Ismail, and Na examine the effect of perceived ethical climate of audit firms, auditor’s exposure to ethics and moral reasoning on ethical judgments. Their finding which shows that moral reasoning has a positive relationship with ethical judgment suggests the need to improve and reform the education system of a country by putting more emphasis on ethics education. In the world of finance, a bank’s liquidity is crucial for performance sustainability and this is shown in the third paper by Geraldina, Rossieta, and Utama who find that conventional commercial banks in Indonesia